An Analysis of EFL Test Takers’ Problems in IELTS Writing Task - Ariani, Nina; Arham, Muhammad (Fakultas Sastra - Universitas Muslim Indonesia, 2020)
IELTS (International English Language Testing System) is one of the English proficiency tests which consists of 4 skills that should be tested including Writing which has two types “writing task 1 and task 2. However, there are many problems that testees face in doing writing such as problem in language use, word choice, punctuation and so on that make them could not pass the test. in this case, the researcher focueses on writing task 1 to know the problems that testees faced. The present study aims at (i) finding out the problems are faced by the testees,(ii) to find out the most frequent problems; and cause of error in language use made by the participants in ELC-IDP Makassar. This study employs a descriptive qualitative approach, and the total number of the samples were 17. The instrument used for this study was archival documents (testees’ writing). In this case the authors clasify the problems of the testee’s writting into four categories: problem in word choice, punctuation, spelling and language use, then language use is identified and clasified into grammatical area: error of verb, noun, pronoun, adjective, adverb, article, preposition, and conjuntion, after that the error analized using procedure of error analysis. The finding indicates that:a total of whole problems are 88 numbers which made by the testees (i) the percentage of problems in word choice is 5 % (4), punctuation 10% (9), spelling 7% (6); (ii) the most frequent problem is error in language use about 78% (69) which the most frequent error is verb area (73%) 50 errors from 69 of total error and; (iii) the causes or error are interference of the learner’s mother tounge, overgeneralization, and false concept hypothesis.